2003
DOI: 10.1007/s11661-003-0228-4
|View full text |Cite
|
Sign up to set email alerts
|

Basal plane texture and flow pattern in friction stir weld of a magnesium alloy

Abstract: The microtextures in a friction-stir-welded magnesium (Mg) alloy, AZ61, with a nugget-shaped stir zone were analyzed by orientation imaging microscopy (OIM). The base material had a (0002) ͗uvi0͘ texture ((0002) parallel to the sheet plane, ͗uvi0͘ parallel to the welding direction). Friction stir welding produced texture components different from those of the base material in the stir zone. Except for the upper surface of the plate, most of the stir zone had a texture with a strong tendency for the (0002) basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
128
2
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(164 citation statements)
references
References 38 publications
(29 reference statements)
15
128
2
4
Order By: Relevance
“…These XRD results show that one-pass and multi-passes FSP have the similar texture and are consistent with the previous texture research on the FSP Mg alloys. [17][18][19] It is confirmed that the specific FSP texture in the stirred zone, where the (0002) basal planes tend to lie surrounding the stirring pin, is persistently maintained even with increasing FSP pass number.…”
Section: Xrd Resultsmentioning
confidence: 69%
“…These XRD results show that one-pass and multi-passes FSP have the similar texture and are consistent with the previous texture research on the FSP Mg alloys. [17][18][19] It is confirmed that the specific FSP texture in the stirred zone, where the (0002) basal planes tend to lie surrounding the stirring pin, is persistently maintained even with increasing FSP pass number.…”
Section: Xrd Resultsmentioning
confidence: 69%
“…Also, the dominantshear direction was everywhere aligned with the tangent to the rotating tool, and aprominent {111} orientation is oriented 70 deg away from plate normal from immediately under the shoulder to the midplane of aw eld. [25] Furthermore, Park et al [11,27] havea pplied FSW to hcp Mg in which slip occursp referentially on the {0002} basal plane, which was shown to align with an ellipsoidal surface in the nugget-shaped SZ. In the friction-stir-processed NABm aterial, the Bfi ber is evidently the dominant shear texture orientation in the TMAZ( the A/B intersection is at one end of the Bfi ber).…”
Section: B Texturei Nt He Sz and Tmazmentioning
confidence: 99%
“…They also reported that these shear textures were present throughoutt he weld zone, and theyc oncluded that refined grains had formed by processes of grain subdivision and the recovery-dominated evolution of high-angle boundaries by dislocation accumulation. Park et al [27] havec onducted FSW of hcp Mg. They showed that the (0002) basal plane, which is the preferred slip plane in Mg, becomes aligned with an ellipsoidal surface in the nugget-shaped SZ.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] However, the coexistence of shoulder-induced and pin-induced textures may decrease the integrity of the weld in subsequent performance. [17][18][19] Therefore, understanding the material flow behavior is of practical importance for optimizing tool design and obtaining welds with high structural efficiencies. [20] Furthermore, a refill FSSW process model has not yet been established.…”
mentioning
confidence: 99%